Basis risk reduction in weather index insurance for rice production in North-West Malaysia - Abdi, Mukhtar Jibril; Zulkafli, Zed; Raffar, Nurfarhana; Khairudin, Nurulhuda (Springer Science and Business Media Deutschland GmbH, 2024)
Weather index insurance allows small-scale farmers to secure income fluctuations caused by adverse weather conditions. However, basis risk, which occurs when the insurance-triggering weather index poorly correlates with the actual yield losses, hinders the demand for such insurance. A higher yield aggregation might reduce basis risk by offsetting localised weather impacts or increase it by oversmoothing. Meanwhile, spatially interpolated rainfall data might reduce basis risk by improving index accuracy or reduce it by introducing interpolation errors. The literature evidence is inconclusive and limited, particularly for small-scale tropical agriculture systems. This work thus aimed to assess the potential risk reduction of hypothetical weather index insurance products for rice production in north-western Peninsular Malaysia, considering both yield aggregation and rainfall interpolation effects. Our results indicated that yield averaged at smaller geographical units produced better correlations with indices and a higher risk reduction potential in only one of four sub-areas studied. Furthermore, the value of interpolated rainfall was only evident at a higher yield aggregation level. These findings underscore the complex interplay between yield aggregation, rainfall interpolation, and basis risk, emphasising the need for context-specific approaches to designing effective weather index insurance products. © The Author(s), under exclusive licence to the International Society of Paddy and Water Environment Engineering 2024.